VEHICLES - Amson-Bradshaw, Georgia (Fact finders, 2019)
Humans have been using vehicles for thousands of years. Explore the technological evolution of vehicles for land, sea and air--from a 10,000-year-old dugout canoe to driverless cars. Discover the challenges engineers face and the improvements they are making to vehicle speeds, materials, and efficiency.